A hypothalamic circuit underlying the dynamic control of social homeostasis - Ding Liu; Mostafizur Rahman; Autumn Johnson; Ryunosuke Amo; Iku Tsutsui-Kimura; Zuri A. Sullivan; Nicolai Pena; Mustafa Talay; Brandon L. Logeman; Samantha Finkbeiner; Lechen Qian; Seungwon Choi; et al. (Nature, 2025)
Abstract Social grouping increases survival in many species, including humans 1,2 . By contrast, social isolation generates an aversive state (‘loneliness’) that motivates social seeking and heightens social interaction upon reunion 3–5 . The observed rebound in social interaction triggered by isolation suggests a homeostatic process underlying the control of social need, similar to physiological drives such as hunger, thirst or sleep 3,6 . In this study, we assessed social responses in several mouse strains, among which FVB/NJ mice emerged as highly, and C57BL/6J mice as moderately, sensitive to social isolation. Using both strains, we uncovered two previously uncharacterized neuronal populations in the hypothalamic preoptic nucleus that are activated during either social isolation or social rebound and orchestrate the behaviour display of social need and social satiety, respectively. We identified direct connectivity between these two populations and with brain areas associated with social behaviour, emotional state, reward and physiological needs and showed that mice require touch to assess the presence of others and fulfil their social need. These data show a brain-wide neural system underlying social homeostasis and provide significant mechanistic insights into the nature and function of circuits controlling instinctive social need and for the understanding of healthy and diseased brain states associated with social context.